La fabrique de la rue mise en images. Retour sur les usages d’un reportage photographique au sein d’un observatoire de la relation formation-emploi - Olivier Liaroutzos; Dominique Vial (Images du Travail, Travail des Images)
On a national and regional level, the analysis of the relationship between training and employment is based on statistical and qualitative studies. The former remains the most common, but the latter is developing and diversifying. Can photography play a significant role in this movement? This question raises issues concerning the method, both for the social sciences and for its fields of application. This question was raised based on an experience of the Provence-Alpes-Côte d’Azur Regional Observatory of Professions that goes back some twelve years. The idea was to gather photographs of the daily life of the Marseilles tramway installation site. An exhibition, an album and conferences made it possible to show the work, the endurance of the body, the diversity of trades, techniques, and organisations. Somewhere between a news report/narrative and an artistic approach, photography reveals a reality which is hardly perceptible when using the usual methods of data collection.